ANALISIS KETERAMPILAN MENYUSUN PARAGRAF DALAM MENULIS CERITA PENGALAMAN PADA SISWA KELAS V DI SDN KEBON JERUK 06 JAKARTA BARAT - Ramdani Akbar; Ezik Firman Syah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning to write personal experiences is a skill in Indonesian language subjects, however in Class V at SDN Kebun Jeruk 06 learning to write personal experiences has not achieved what is expected in writing personal experiences. The aim of this research is to describe the aspects of unity, coherence and completeness of composing paragraphs in writing experience stories for Class V students. Qualitative descriptive research method with concept or content analysis. Data collection techniques use interviews, observation and documentation. Data analysis techniques for drawing percentage conclusions. Based on the results of the researcher's data, two students who experienced difficulties, namely ALY, who experienced difficulty in creating aspects of completeness so that these aspects were not fulfilled in the next paragraph, GFR students experienced difficulties in determining aspects of unity so that GFR created two aspects of cohesion in one paragraph. Based on the results of this research, fifth grade students at SDN Kebon Jeruk 06 are able to compose paragraphs to write experience stories, in terms of aspects of paragraph creation, students are able to differentiate the types of aspects that make up paragraphs, the experience stories created by students are easy to understand to read, based on The percentage explained above shows that class V students at SDN Kebon Jeruk 06 got a score above 70%, which indicates that the student got a good predicate (B) and was able to compose paragraphs in writing experience stories.